The comparative performance of active and passive equity-only funds in South Africa - Naidoo, Jayendran (My University, 2017)
The world has and is still witnessing a tremendous growth in various categories of mutual funds. Active fund managers continue to grow globally with many asking for exorbitant fees for their research and investment services. Equally, passive funds in the form of Exchange Traded Funds (ETF's) and index trackers have also continued to grow. This massive growth does not preclude funds domiciled in South Africa. Passive investments have grown by about 51 percent a year in the last 10 years in South Africa. As at 2016, there are over 3000 mutual funds domiciled in South Africa. Amidst these growing funds is the ongoing debate relating to the question of which fund management style yields the best outcome. The global debate relating to passive versus active fund management has raged for decades with no clear winner. The extant literature provides mixed evidence on the competitive advantage to either investment strategies. Surprisingly, the evidence for South Africa remains scanty, with a handful of authors addressing the issue. This study therefore, sets out to examine the comparative performance of all equity-only active mutual and passive funds domiciled in South Africa. In addition, it analyses the performance persistence of active and passive funds in different business cycles. A major contribution of this study is that it examines, for the first time, the applicability of the Fama-French five factor model on South African mutual funds. It also employs a battery of econometric methods to address the issue at hand. Relying on data from 2003 to 2016, the study presents evidence that both active and passively managed mutual funds do not earn abnormal returns but rather underperform the benchmark. However, the active portfolio performs relatively better than the passive portfolio, although both underperform the market. The study also documents evidence of time-varying performance; both active and passive funds record their worst underperformance during periods of financial crisis. The study also shows that passive portfolios tend to track the market performance more than active portfolios and that both fund categories tend to be sensitive to global market movements, suggesting that global factors matter for the riskiness of these funds. Finally, it is shown that in terms of driving factors, both active and passive fund managers generally give more preference to small cap returns than large cap returns. In addition, they are more growth oriented, as indicated by the negative coefficients for the HML factor.
Thesis (M.M. (Finance & Investment)--University of the Witwatersrand, Faculty of Commerce, Law and Management, Wits Business School, 2017
Keywords: Mutual funds--South Africa; Investments--South Africa--Mathematical models